(untitled) (Journal of the College of Basic Education, 2022)
The aim of the research is to prepare complex exercises for the purpose of developing knowledge and performing some individual defensive moves for the players of the University of Baghdad handball team. The research hypothesis was: There are statistically significant differences between the results of the pre and post tests in the development of knowledge and the performance of some individual defensive moves for the players of the University of Baghdad handball team.